From tooth to hoof: treponemes in tissue-destructive diseases - Edwards,AM; Dymock,D; Jenkinson,HF (J.Appl.Microbiol., 2003)
With the advent of new molecular and immunological tools, there is better understanding of the roles that difficult to cultivate bacteria, and not-yet-cultivated bacteria such as spirochaetes, play in polymicrobial diseases. Only relatively recently have studies implicated Treponema spirochaetes in human periodontal disease, a destructive condition of the tissues supporting the teeth. A number of different Treponema species have been isolated and their surface protein components that mediate adhesion, cytotoxicity, and tissue damage have been characterized. More recently Treponema strains closely related to human oral isolates have been cultivated from active lesions of digital dermatitis, an ulcerative condition affecting the feet of cows and sheep. This condition, like periodontal disease, appears to have a polymicrobial aetiology in which enrichment for Treponema may play a crucial part. This article reviews the known mechanisms by which Treponema interact with eukaryotic host cells and tissue proteins, and how these interactions may contribute to pathogenic diversity